Capital Structure Determinants In The Era Of Digital Economy: Evidence From Technology Firms - Alfiana Alfiana; Klemens Mere; Farini Limbong (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2026)
The rapid evolution of the digital economy has reshaped the financial structure and strategic financing decisions of technology-based firms. This study investigates the determinants of capital structure among technology firms operating in the digital era, focusing on the interplay between traditional financial variables and new digital-driven factors. Using panel data from publicly listed technology companies between 2015 and 2024, this research applies multiple regression and fixed-effects models to examine the influence of firm size, profitability, asset tangibility, growth opportunities, liquidity, and digital innovation intensity on leverage ratios. The results indicate that while profitability and asset tangibility remain significant predictors consistent with pecking order and trade-off theories, digitalization level and intangible asset intensity introduce new dynamics in capital structure decisions. Firms with higher digital innovation and intangible assets tend to rely more on equity financing due to lower collateral values and greater market uncertainty. These findings provide empirical insights for investors, managers, and policymakers on optimizing capital structure strategies within the evolving context of digital transformation.